THE COLLABORATIVE DESIGNING OF A PERSONALIZED HYBRID LMS USING A VIRTUAL MACHINE IN A CLOUD ENVIRONMENT - Lina Čeponienė; Péter Galambos; Tamás Haidegger; Dariusz Mikulowski; Branislav Mišota; Oliver Moravcik; Enikő Nagy; Mariya P. Shyshkina; Pavel Smolka; Stefan Svetsky (Інформаційні технології і засоби навчання)
A teacher currently needs to acquire a huge amount of educational information and knowledge as part of his/her practice for the purposes of teaching, self-study, publishing, research, language support and related activities. In the academic environment, so-called learning management systems (LMSs), especially Moodle in the European Union, have proven suitable for the processing of educational content under e-Learning. LMSs usually function as online platform, at the same time as a supplement to academic information systems (AIS) on the local servers of universities. These are used by a larger number of participants, so these do not always meet the pedagogical needs of the teacher in all the activities he/she does. For example, these do not allow multilingual support, multiple searches and mass processing of e-Learning content. There are a large number of articles in the scientific literature describing the design of add-on modules for LMS. The authors offer their own approach to solving the problem of processing educational information to support a virtual team's work. As part of collaborative research in the field of technology-enhanced education and e-Learning design, the international team in the V4 EDUPORT project is implementing a personalized hybrid system on the IT infrastructure consisting of a specially designed desktop application WPad or web application (PIKS) and a common shared remote computer (virtual computer on a cloud server with Windows 2022). In this paper, the researchers share their experiences gained with their universities' academic LMSs (Moodle and AIS) and compare their personalization capabilities level to the teacher level and their use in the cloud. Part of current and future research is the development of the PIKS internet application, which operates as a multi-functional communication channel for e-Learning purposes (including use for the visually impaired).